Urolithin A regulates gut: liver axis to ameliorate alcohol-associated liver disease - Ghosh, Sweta; Singh, Rajbir; Vanwinkle, Zachary Matthew; McClain, Craig James; Vatsalya, Vatsalya; Haribabu, Bodduluri; Vemula, Praveen Kumar; Jala, Venkatakrishna Rao (Frontiers in Pharmacology, 2026)
Background and AimsExcessive alcohol consumption poses a significant global health concern, ranking as the world’s third-largest risk factor for diseases and disabilities, contributing to 5.9% of all deaths worldwide. Among various disorders linked to alcohol misuse, alcohol-associated liver disease (ALD) is the most prominent. ALD patients often exhibit increased intestinal permeability, systemic inflammation, gut dysbiosis, and hepatic steatosis. No FDA-approved therapies are available to treat ALD or to resolve the pathological domains of alcohol-induced gut barrier dysfunction, inflammation, and steatosis. The goal of this study is to investigate the potential therapeutic role of the microbial metabolite Urolithin A’ (UroA), in alleviating ALD.MethodsCaco-2 (monolayer colon epithelial) cells and AML12 (hepatocytes) cells were used to test the protective activities of UroA against EtOH-induced gut barrier dysfunction and lipid accumulation in vitro. Preclinical ALD mouse models were used to test the therapeutic potential of UroA against EtOH exposure. Additionally, we generated cell-specific deletion mice with aryl hydrocarbon receptor (AHR) deletion to define the role of intestinal epithelial cell AHR in UroA-mediated protective activities against ALD.ResultsThe results presented here demonstrate the efficacy of UroA as a potential therapeutic agent to protect against EtOH-induced disruption of tight junction proteins, inflammation, and lipogenesis both in vitro and in vivo models.ConclusionOur findings suggest that the simultaneous targeting of gut barrier dysfunction, inflammation, and hepatic steatosis by treatment with UroA may offer new possibilities for combating ALD. Moreover, our results suggest that UroA-mediated protective activities against EtOH-induced gut barrier dysfunction and inflammation in ALD are dependent on intestinal epithelial cell-AHR.